A geometric analysis of slip rate variation with depth in listric normal faults - Zhang, Yao (Frontiers in Earth Science, 2023)
Fault slip rates are critical parameters for assessing regional strain accumulation and seismic hazards. Previous investigations on fault slip rates primarily concentrated on shallow depths or along the strike of the fault, neglecting the variation with depth. This study focuses on listric normal faults, commonly observed in tectonic extensional zones, and investigates the variation of slip rates with depth. The relationships between slip rates along different fault segments are derived based on the inclined shear geometric models. The study finds that slip rates on different segments of listric normal faults are generally not equal and depend on the type of bend (concave or convex), the dip angles of the fault segments and axial surfaces. Inferring regional horizontal extension solely from shallow segment displacements or growth strata thickness may lead to inaccurate conclusions. In accordance with the methodology outlined in this paper, slip rates at various depths along the Chengnan Fault for the three time intervals: 24.6–33 Ma, 33–43.5 Ma, and 43.5–65 Ma, are estimated. The results of this study offer valuable insights into the kinematics of listric normal faults, facilitating a better comprehension of the discrepancy between slip rates measured at surface and slip rates measured at depth.